A New 6.4 M Diameter By 10.2m Long Ball Mill At Toquepala Concentrator - H. Walqui; A. Buendía (Society for Mining, Metallurgy & Exploration, 2003)
The Toquepala concentrator expansion project incremented the capacity of the existing concentrator by 15,000 Metric tons per day (t/d), from 45,000 to 60,000 t/d. The plant is located in southern Peru,1,200 km southeast of Lima. The implementation plan for the expansion project was based upon an engineering and procurement contract, and a construction contract. The overall Project Management was by Southern Peru Copper Corporation (SPCC). The expansion followed a very aggressive schedule that considered a construction period of only ten months, with minimum interference to the existing facilities. Major equipment was purchased during basic engineering. This paper details the design, construction, and commissioning of the 6.4 m diameter by 10.2 m long ball mill, and the performance of the milling circuit during the first two months of operation.